The new rules of marketing & PR : : how to use social media, online video, mobile applications, blogs, news releases & viral marketing to reach buyers directly - Scott, David Meerman ([Rego Park] :: Your Coach Digital, 2014)
The benchmark guide to marketing and PR, updated with the latest social media and marketing trends, tools, and real- world examples of success The New Rules of Marketing & PR 4th Edition is the pioneering guide to the future of marketing, an international bestseller with more than 300, 000 copies sold in over 25 languages. It offers a step-by-step action plan for harnessing the power of modern marketing and PR to communicate with buyers directly, raise visibility, and increase sales..
Keywords: Public relations; Internet marketing